2005
DOI: 10.1177/0149206305279759
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Individuals Attracted to Organizations?

Abstract: Applicant attraction is vital to the success of an organization. Despite its importance, however, research on it has tended to proceed in a relatively piecemeal way. Accordingly, the authors present a framework for attraction research through an examination of the underlying relevant theories. Specifically, they identify three overarching metatheories focusing on environment processing, interactionist processing, and self-processing that form the basis for their theoretical model. The authors conclude with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
255
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(286 citation statements)
references
References 62 publications
4
255
0
3
Order By: Relevance
“…Similarly, advertisements in recruitment processes for internships aim to inform students about an organization, emphasizing its positive attributes to raise their desire to work for it, impacting on their preference in choosing to apply for its selection process. Reference [22] found that repeated exposure of objects to individuals leads to increased ratings and positive perceptions about them. So, the more a student is acquainted with a company, the more positive will be his/her response to recruiting calls [23] and the higher the attractiveness rate to participate in their selection processes [24].…”
Section: Recruiting Undergraduate Students Onlinementioning
confidence: 99%
“…Similarly, advertisements in recruitment processes for internships aim to inform students about an organization, emphasizing its positive attributes to raise their desire to work for it, impacting on their preference in choosing to apply for its selection process. Reference [22] found that repeated exposure of objects to individuals leads to increased ratings and positive perceptions about them. So, the more a student is acquainted with a company, the more positive will be his/her response to recruiting calls [23] and the higher the attractiveness rate to participate in their selection processes [24].…”
Section: Recruiting Undergraduate Students Onlinementioning
confidence: 99%
“…As a result, management scholars almost universally refer to either Spence's (1973) examination of signaling in job markets or Ross's (1977) study of managerial incentives as signals to describe the theory's central tenets. Over time, however, the key concepts underlying signaling theory have become blurred (Highhouse, Thornbury, & Little, 2007), causing some to argue that signaling theory is ill defined (Ehrhart & ziegert, 2005).…”
Section: Signaling Theorymentioning
confidence: 99%
“…Research cites that potential applicants interpret many recruitment related information as signals about organizational and employer's characteristics (Collins & Stevens, 2002). Signalling theory has the capacity to understand the impact of many factors that may act as predictors for applicant attraction (Ehrhart and Ziegert, 2005), social identity theory and self-categorization theory have the capability to facilitate researchers to comprehend the conditions under which potential incumbents see some signals in a more positive way than the other. The understanding of the signalling theory shall facilitate the firms to understand the psychological processes that potential incumbents get involved into when they judge the employer attractiveness.…”
Section: Conceptual Framework Of Signalling Theorymentioning
confidence: 99%